Contribuição ao estudo de controle plantwinde: controle indireto e coordenação de controladores descentralizados - Hori, Eduardo Shigueo (2005)
The design of plantwide control systems has received increasing attention in the last years. The modern chemical plants usually consist of hundreds of interconnected elementary processes and unit operations (large scale complex systems). These plants are usually characterized and dominated by large and highly integrated and automatized installations, with several recycle streams, more heat integration and fewer inventories. All these factors lead to high interactions among the subunits caused by material and energy recycle and, consequently to the need for a perspective beyond individual units. The plantwide system control design procedure is not clear and the literature is scarce about this issue, comparatively with simple unit design. In this way, a large challenge for the Chemical Engineer in the last decades has been designing control systems that operate with safety and bring the performance objectives needed to control these complex plants. The main objective of this project is to study the plantwide control problem aiming, particularly, the choice of controlled variables and the coordination of several decentralized controllers to avoid conflicting control actions. The results presented in this thesis show that the work objective was reached successfully, due to a significant contribution to plantwide control study.